Sistem Informasi Akuntansi Perhitungan Biaya Produksi Ternak Ayam Broiler Kemitraan Berbasis Web - Imam Soleh Marifati, SE, MM; Ubaidillah Ubaidillah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2023)
Broiler livestock in a partnership is one of the efforts to make it easier for farmers to run their business. The objective of this partnership is increasing livestock productivity along with business efficiency and in turn improve the welfare of farmers. From the core company side in the partnership, this core company records the production costs for each plasma. This is in order to determine profit sharing from harvesting livestocks. In order to support the recording of the plasma’s production costs carried out by the core company, an information system can be used so that the recording process can be better. Research on the development of an accounting information system for calculating the cost of production of broiler livestocks is needed. An application that is suitable for this purpose can be produced. In this study the authors developed an application to calculate the production costs of broiler chickens that can be used by core company